2000
DOI: 10.1111/1467-8624.00148
|View full text |Cite
|
Sign up to set email alerts
|

Dual Representation and  Young Children's Use of Scale Models

Abstract: To use a symbolic object such as a model, map, or picture, one must achieve dual representation; that is, one must mentally represent both the symbol itself and its relation to its referent. The studies reported here confirm predictions derived from this concept. As hypothesized, dual representation was as difficult for 2 1/2-year-olds to achieve with a set of individual objects as it was with an integrated model. Decreasing the physical salience of a scale model (by placing it behind a window) made it easier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
259
0
14

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(295 citation statements)
references
References 45 publications
12
259
0
14
Order By: Relevance
“…Therefore, we can conclude that the infants responded neurologically different to the observation of video compared to live actions probably due to a different visual experience with 2D stimulus presentation in contrast to real 3D object presentation (Shimada and Hiraki, 2006). Additionally, research revealed that infants under 3 years of age find it difficult to symbolize 2D scale models as 3D real objects (DeLoache, 2000). Therefore, it could be suggested that less mu suppression in the video group is the result of inadequate visual processing.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, we can conclude that the infants responded neurologically different to the observation of video compared to live actions probably due to a different visual experience with 2D stimulus presentation in contrast to real 3D object presentation (Shimada and Hiraki, 2006). Additionally, research revealed that infants under 3 years of age find it difficult to symbolize 2D scale models as 3D real objects (DeLoache, 2000). Therefore, it could be suggested that less mu suppression in the video group is the result of inadequate visual processing.…”
Section: Discussionmentioning
confidence: 87%
“…For example, they can see a toy car as a representation of real cars and as an object in itself. DeLoache (1995DeLoache ( , 2000 called this emerging differentiation of representations dual representation. Dual representations enable children to reflect on and operate explicitly on representations as tokens of reality.…”
Section: Differentiation Of Representationsmentioning
confidence: 99%
“…Furthermore, children in another experiment who had less opportunity to interact with the model (by placing it behind a window) were more effective at searching in the real room. DeLoache (1995DeLoache ( , 2000 notes that although experience typically facilitates performance, in this case, experience may have changed the way children viewed the model room. Although a lower level of experiencebased salience allowed children to view the model room as a representation, a higher level of interaction with the object prevented this more sophisticated understanding.…”
Section: Experiments 1: Action-involving Experiencementioning
confidence: 99%